BANDING IN AORTIC STENT-GRAFT FIXATION IN EVAR - Utikal, Petr; Kocher, Martin; Bachleda, Petr; Drac, Petr; Cerna, Marie; Buriankova, Eva (Biomedical papers, 2004)
The authors describe the method of surgical aortic banding for better stent-graft fixation in cases of problematic aortic neck in the endovascular infrarenal aneurysms repair.
Keywords: Aorta/Aneurysms/Repair/Endovascular/Stent-graft/Fixation/Endoleak/Migration/Complications